The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12524-011-0110-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Priorities for Sustainable Forest Management in the Sikkim Himalaya, India: A Remote Sensing Based Approach

Abstract: Sikkim is a small, mountainous, Indian state (7,096 km 2 ) located in the eastern Himalayan region. Though a global biodiversity hotspot, it has been relatively less studied. A detailed forest type, density and change dynamics study was undertaken, using SATELLITE remote sensing data and intensive field verification. The landscape was found to be dominated by alpine and nival ecosystems, with a large portion above the tree line, considerable snow cover, and a sizeable area under forest cover (72%, 5,094 km 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, between forest types, the low-altitude forests completely lacked trees above 93 cm diameter, a scenario undesirable for a sustainable forest. The finding could be associated with forest degradation and deforestation reported by earlier studies [47,61]. One potential factor for the absence of large trees could be the practice of cardamom cultivation mainly in the low-altitude forest of Sikkim.…”
Section: Forest Structure: Stem Diameter Stem Density and Basal Areamentioning
confidence: 67%
See 2 more Smart Citations
“…However, between forest types, the low-altitude forests completely lacked trees above 93 cm diameter, a scenario undesirable for a sustainable forest. The finding could be associated with forest degradation and deforestation reported by earlier studies [47,61]. One potential factor for the absence of large trees could be the practice of cardamom cultivation mainly in the low-altitude forest of Sikkim.…”
Section: Forest Structure: Stem Diameter Stem Density and Basal Areamentioning
confidence: 67%
“…with Mount Kanchendzonga-the third highest peak in the world. The complex topography and enormous altitude are characterized by 12 major vegetation types, from a tropical warm broad-leaved forest at the lowest altitude to alpine meadow at the highest altitude [47]. It has a subtropical to temperate climate, with annual rainfall between 2700 mm to 3200 mm, and the mean annual temperature (MAT) varies from 8.4 • C to 23.2 • C [48].…”
Section: Study Area Description and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regeneration of the plant is the key ecological process in a forest ecosystem in which seeding and sprouting of woody species are involved (Pratt et al 2012). One of the most important problems that mountainous forests are experiencing is poor regeneration (Karauchi et al 2000), which is especially observed in subalpine forests in Eastern Himalaya (Tambe et al 2011;Pandey et al 2018) as well as in Western Himalaya (Rai et al 2012). Poor regeneration and naturally slow growing nature of Larix griffithiana are documented in subalpine forests in Sikkim Himalaya (Tambe et al 2011) and absence of seedlings and saplings of the species has been recorded in temperate forests in Lachung Range of the Sikkim Himalaya (Subba et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sustainability of populations with inadequate number or lack of regenerating individuals has been reported to be challenging for several species of subalpine trees. Examples include Larix potaninii in China (Taylor et al 1996;Cui et al 2017;Liang and Wei 2020), Larix griffithiana in Sikkim, India (Tambe et al 2011;Subba et al 2015), and Bhutan (Moktan 2010); and for many other species in the eastern Himalaya (Pandey et al 2018), Nepal Himalaya (Vetaas 2000;Shrestha et al 2007;Kunwar 2011;Sujakhu et al 2013;Maren et al 2015;Suwal et al 2016), and western Himalaya (Rai et al 2012). Therefore, for the effective conservation of the typical Himalayan vegetation of Larix forests, efforts need to be concentrated both locally and regionally.…”
Section: Parametermentioning
confidence: 99%